2018
DOI: 10.1159/000490865
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Signaling Pathway Inhibition Attenuates Airway Inflammation and Remodeling in Rats with Asthma

Abstract: Background/Aims: Thymic stromal lymphopoietin (TSLP) is a cytokine that plays diverse roles in the regulation of immune responses. However, a detailed understanding of the TSLP signaling pathway in asthma remains elusive. In this study, we aimed to investigate the role of the TSLP signaling pathway in asthma and its effect on airway inflammation and remodeling. Methods: Forty Sprague Dawley (SD) rats were evenly classified into control, asthma, IgG2a mAb and anti-TSLP mAb groups. Ovalbumin (OVA)-induced asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Asthma is increasing in prevalence, with substantial morbidity [5,12,41,42]. The etiology of asthma involves inflammation, remodeling and AHR with an important role for ASM [5,9,10,12,[43][44][45][46][47]. Evidence from clinical studies suggest sex differences in the prevalence of asthma, and a potential role of sex steroids in the pathophysiology [4][5][6][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is increasing in prevalence, with substantial morbidity [5,12,41,42]. The etiology of asthma involves inflammation, remodeling and AHR with an important role for ASM [5,9,10,12,[43][44][45][46][47]. Evidence from clinical studies suggest sex differences in the prevalence of asthma, and a potential role of sex steroids in the pathophysiology [4][5][6][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelium‐generated cytokine TSLP was known as the master switch of initiating and maintaining allergic asthma . We have previously demonstrated that production of TSLP was increased in the lung of asthmatic mice and TSLP level is associated with DC maturation and the extension of Th2‐biased inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic inflammation of the airways characterized by the infiltration of inflammatory cells, inflammation, hyperresponsiveness and remodeling ( Murdoch and Lloyd, 2010) that can be induced or exacerbated by exposure to environmental triggers (Hardy et al, 2015). Its symptoms include excessive production of mucus leading to airway obstruction (Doeing and Solway, 2013) and is often accompanied by infiltration of the airways by eosinophils, mast cells and lymphocytes, thickening of the bronchial walls, and hypertrophy/hyperplasia of airway smooth muscle (Cheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%